SEPANNING MINIMUM TREE APPLICATIONS IN DELIVERY NEWSPAPER USING TURBO PASCAL 7 - Herman Herman; Ire Puspa Wardhani, Skom, MMSi (Jurnal Sistem Informasi, 2002)
Effectiveness in a job is needed more than anything else, all these modern securedEffectiveness requires time in order to support the performance of a work. TheEffectiveness of time is one of them is in determining the route of delivery ofnewspapers to its customers that require delivery of a very long time if it has enoughcustomers.From penyelesaianyang each use the manual are still many shortcomings, for it wasonce created a new settlement system is expected to overcome the existingshortcomings.